2012
DOI: 10.1242/jeb.063040
|View full text |Cite
|
Sign up to set email alerts
|

The hydrodynamic function of shark skin and two biomimetic applications

Abstract: SUMMARYIt has long been suspected that the denticles on shark skin reduce hydrodynamic drag during locomotion, and a number of manmade materials have been produced that purport to use shark-skin-like surface roughness to reduce drag during swimming. But no studies to date have tested these claims of drag reduction under dynamic and controlled conditions in which the swimming speed and hydrodynamics of shark skin and skin-like materials can be quantitatively compared with those of controls lacking surface ornam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
194
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(203 citation statements)
references
References 36 publications
8
194
1
Order By: Relevance
“…The fins' parasite drag coefficient likewise includes a similar friction factor. The coefficient K and exponent α (>0) parameterize the fluid's friction as the combined result of a shark's denticulated skin and swimming motions on the body (Oeffner and Lauder, 2012;Shelton et al, 2014). Recent studies of shark hydrodynamics make it clear that the interactions of the boundary layer generated by the skin's denticles interacts with the flows created by the tail's motions in ways that do not always minimize body drag, and moreover in ways that are difficult to quantify in simple formulas such as in Eqn 3 (Shelton et al, 2014).…”
Section: Modelling the Energetic Consequences Of Changing Water Densitymentioning
confidence: 99%
“…The fins' parasite drag coefficient likewise includes a similar friction factor. The coefficient K and exponent α (>0) parameterize the fluid's friction as the combined result of a shark's denticulated skin and swimming motions on the body (Oeffner and Lauder, 2012;Shelton et al, 2014). Recent studies of shark hydrodynamics make it clear that the interactions of the boundary layer generated by the skin's denticles interacts with the flows created by the tail's motions in ways that do not always minimize body drag, and moreover in ways that are difficult to quantify in simple formulas such as in Eqn 3 (Shelton et al, 2014).…”
Section: Modelling the Energetic Consequences Of Changing Water Densitymentioning
confidence: 99%
“…But one important effect of the denticles is to enhance thrust, and not simply to reduce drag. It was later proved by Oeffner et al [86] that the mimicked shark denticles on the suit as seen in Fig. 13 had no beneficial loco-motor effect which should have helped propel the body, but in this case, it can only reduce the skin friction to a certain extent.…”
Section: Friction-reducing Sharkskinmentioning
confidence: 97%
“…Such denticle structure is common on the body, fins, and tail, although denticles of this species on the head have a different morphology. Scale bar, 50 lm [86] plants. Wilke et al [88] in their attempt to diminish drag and resistance to flow of currents for these applications were inspired from the evolved scales of fast-swimming sharks.…”
Section: Friction-reducing Sharkskinmentioning
confidence: 99%
“…Biologically inspired materials might also lead to swifter swimmers. Swimwear companies such as Speedo have claimed to make shark-skin-like fabrics, but George Lauder, an ichthyologist at Harvard University, has demonstrated that the Speedo suits that were banned after the 2008 Olympics do not contain the microscopic shark scales, called denticles, that reduce drag 5 . Using a threedimensional (3D) printer, Lauder last year constructed true artificial skin of the shortfin mako shark (Isurus oxyrinchus) and showed that it not only limits drag but also increases thrust 6 .…”
Section: When Appearance Is Deceptivementioning
confidence: 99%